An Anthology of his poetry - Unamuno, Miguel de (Aris and Phillips Hispanic Classics Ser., 2015)
Miguel de Unamuno, one of Spain's foremost literary figures, is better known for his essays and novels than for his poetry. Yet it was as a poet that he wished to be remembered and it is in his poems that he reveals the most intimate and sensitive part of his complex personality. To truly get to know Unamuno as creator it is necessary to read his poetry. This anthology of 50 poems, though modest in comparison to his large poetic output, offers the reader some of his most characteristic poems, with an English version prepared by a well-known Unamuno scholar. The English renderings are sufficiently free to allow for the use of rhyme and regular metre, but strive to capture Unamuno's highly personal way of looking at our human circumstance and destiny. In effect the anthology offers a way of approaching Unamuno that differs significantly from an approach via his prose works: it projects a more meditative and warm-hearted individual than the combative Unamuno of popular perception. The 50 poems, each with a short commentary relating it to Unamuno's personal circumstances and to his thought, are arranged under six headings: (1) Family and Home; (2) God and Mortality; (3) The Land; (4) Exile; (5) Language and Poetry; (6) Philosophical Meditations. The anthology thus offers a microcosm of Unamuno's poetic world and should be useful to those who have little or no knowledge of him. It provides a way of learning something about the man and the writer through a part of his production that has received less attention than it deserves and which projects a significantly different image from the widespread view we have of him. The poems are preceded by a substantial introduction which explores the importance and relevance of Unamuno's poetry, his major themes, and his style.